2014
DOI: 10.1161/atvbaha.113.301655
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines in Atherosclerosis

Abstract: Chemokines play important roles in atherosclerotic vascular disease. Expressed by not only cells of the vessel wall but also emigrated leukocytes, chemokines were initially discovered to direct leukocytes to sites of inflammation. However, chemokines can also exert multiple functions beyond cell recruitment. Here, we discuss novel and recently emerging aspects of chemokines and their involvement in atherosclerosis. While reviewing newly identified roles of chemokines and their receptors in monocyte and neutrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
145
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(156 citation statements)
references
References 80 publications
2
145
0
Order By: Relevance
“…Cytokines elevated in psoriasis patients include TNFα, IL12/23, IL1β, IFNγ, and IL17 (42) and are often targeted in a psoriasis treatment regimen. These cytokines have been demonstrated to be of crucial importance for macrophage plasticity in acute or chronic aspects and in regard to atherogenesis (11,19,43,44). However, since isolated macrophages in our study were differentiated under cytokine neutral conditions, a genetic preconditioning toward the proatherosclerotic phenotype may also modulate these characteristics.…”
Section: Discussionmentioning
confidence: 83%
“…Cytokines elevated in psoriasis patients include TNFα, IL12/23, IL1β, IFNγ, and IL17 (42) and are often targeted in a psoriasis treatment regimen. These cytokines have been demonstrated to be of crucial importance for macrophage plasticity in acute or chronic aspects and in regard to atherogenesis (11,19,43,44). However, since isolated macrophages in our study were differentiated under cytokine neutral conditions, a genetic preconditioning toward the proatherosclerotic phenotype may also modulate these characteristics.…”
Section: Discussionmentioning
confidence: 83%
“…Recent studies have suggested that pathologic T cell driven inflammatory responses play a key role in the progression of athero-. These T cell-related inflammatory responses involve interactions between cytokines, adhesion molecules, and chemokines 4,5) . Mach et al have demonstrated that T cell-activating C-X-C chemokines are highly expressed in human atheroma-associated cells throughout all stages of plaque development 6) .…”
Section: Introductionmentioning
confidence: 99%
“…13 Multiple chemokines have been implicated in this, including fractalkine receptor CX3CR1, which promotes lesion progression. 10,19 CX3CR1 is expressed on leukocytes, including monocytes, dendritic cells, T cells, and natural killer cells, 20 but also nonmyeloid cells such as aortic smooth muscle cells. 21 CX3CR1 deficiency (CX3CR1 2/2 , mostly studied in CX3CR1 gfp/gfp mice 22 ) decreases the development of atherosclerotic lesions in Apoe 2/2 mice.…”
mentioning
confidence: 99%